Ulcerated infantile hemangioma - Belo, Nídia (2019)
Infantile hemangiomas are the most frequent vascular tumors in pediatric age. Diagnostic can be challenging due to variable clinical presentation and natural history. Most cases have a favorable evolution. Treatment may be required according to tumor location, extension, and complications. Propranolol is an effective and safe treatment. The case of an infant with perianal ulcerated hemangiomas treated with propranolol with clinical improvement is reported.